2019
DOI: 10.4103/jomfp.jomfp_74_18
|View full text |Cite
|
Sign up to set email alerts
|

Nonsyphilitic occurrence of mulberry molars: A rare case report

Abstract: Developmental defects of enamel may range from slight abnormalities of the tooth's color, shape and size to a complete absence of the enamel. Permanent first molar may show large variations in their morphological features and forms. Such changes may be in the form of anomalous cusps or variations in the occlusal surface showing globular shaped additional cusps and also increased in number of roots. However, to the best of our knowledge, this is the first nonsyphilitic case with the occurrence of multiple globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In both patients, the mulberry teeth were present in the absence of congenital syphilis, a known association with this particular tooth anomaly. 25 Small numbers limited the ability to statistically compare differences between affected and unaffected sides.…”
Section: Resultsmentioning
confidence: 99%
“…In both patients, the mulberry teeth were present in the absence of congenital syphilis, a known association with this particular tooth anomaly. 25 Small numbers limited the ability to statistically compare differences between affected and unaffected sides.…”
Section: Resultsmentioning
confidence: 99%
“…A rare case of no syphilitic mulberry first molars was described in dental clinic in Raichur, but it involves all the first molars. [ 15 ] A case of 15-year-old girl was reported by Sedano et al, where the defected teeth were again the first permanent molars. [ 4 ] Rodrigo et al reported a case of Hutchinson teeth in a 31-year-old woman which history did not reveal any clues to syphilis and the T pallidum particle agglutination test was negative in both the patient and her mother.…”
Section: Discussionmentioning
confidence: 99%
“…This is a syphilitic stigmata [9] . Mulberry molars have also been reported in cases without syphilis [10] . 8.…”
Section: Cottage Cheese Appearancementioning
confidence: 97%